Persepsi Peserta Didik SMP terhadap Penerapan Kurikulum Merdeka di Mata Pelajaran IPA - Arif, Rifda Nur Hikmahwati; M., Fitrah Sukmadewi; Samputri, Salma; Arif, Rifda Mardian (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2024)
This study aims to determine the perceptions of junior high school students towards the implementation of the independent curriculum in science subjects. This research uses descriptive statistics. The research subjects consisted of 58 students in two junior high schools, namely SMPN 2 Pattalassang and SMPN 3 Makassar. The data analysis technique uses descriptive statistics by calculating the percentage of each indicator. The results showed that the majority of students had a positive perception of science learning in the Merdeka Curriculum, with 53.5% of students stating Agree (36.1%) and Strongly Agree (17.4%). The most prominent indicator is “Science teachers facilitate active discussion and question and answer” with a total of 77.6% positive responses, followed by “Science assessment includes practice” (72.5%) and “Teacher feedback helps how to learn” (65.6%). However, motivation to explore science outside of school hours is still low. Positive responses totaled 29.3%, neutral responses totaled 41.7%, and negative responses totaled 4.8%.